2021
DOI: 10.3389/fncel.2021.668008
|View full text |Cite
|
Sign up to set email alerts
|

Large Acid-Evoked Currents, Mediated by ASIC1a, Accompany Differentiation in Human Dopaminergic Neurons

Abstract: Acid-sensing ion channels (ASICs) are proton-gated Na+ channels. They contribute to synaptic transmission, neuronal differentiation and neurodegeneration. ASICs have been mainly characterized in neurons from mice or rats and our knowledge of their properties in human neurons is scarce. Here, we functionally characterized ASICs in differentiating LUHMES cells, a human mesencephalic cell line with characteristics of dopaminergic neurons. We find that LUHMES cells express functional ASICs, predominantly homomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 55 publications
(88 reference statements)
2
11
0
Order By: Relevance
“…Moreover, the data of quantitative real-time PCR and the proton affinity parameters point to the prevalence of homomeric ASIC1a channels. Indeed, pH 50 and pHSSD 50 , equal to 6.65 and 7.19, respectively, as well as desensitization time constant (τ des ), equal to 0.49 s at the pH 5.0 stimulus, perfectly correspond to the known values for homomeric ASIC1a [12,28,30]. The established dominance of ASIC1a is consistent with previous reports of its involvement in neurodifferentiation where this channel apparently modulates maturation of dendrites and neurites and dopamine secretion in dopaminergic neurons [10][11][12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the data of quantitative real-time PCR and the proton affinity parameters point to the prevalence of homomeric ASIC1a channels. Indeed, pH 50 and pHSSD 50 , equal to 6.65 and 7.19, respectively, as well as desensitization time constant (τ des ), equal to 0.49 s at the pH 5.0 stimulus, perfectly correspond to the known values for homomeric ASIC1a [12,28,30]. The established dominance of ASIC1a is consistent with previous reports of its involvement in neurodifferentiation where this channel apparently modulates maturation of dendrites and neurites and dopamine secretion in dopaminergic neurons [10][11][12].…”
Section: Discussionsupporting
confidence: 89%
“…Ligands were applied only after a stable response to pH 6.0-induced activation was achieved. Amiloride, which finds a medical application as a K + -sparing diuretic agent, is a non-specific blocker τ des of homomeric ASIC1a channels was previously reported to be in the range from 1 to 2 s [12,28,29], while τ des < 1 s was reported to be inherent to heteromeric ASIC1a/ASIC2a channels [28]. However, for heteromeric ASIC1a/ASIC2a channels, it was also shown that with greater acid stimulus τ des significantly increases and approaches a value close to 1 s. In RA-treated cells, τ des significantly decreased with stronger acid stimulus and matched perfectly to the value for homomeric ASIC1a channels [28].…”
Section: Pharmacological Characteristics Of Asic1a In Ra-treated Sh-sy5y Cellsmentioning
confidence: 99%
“…A third avenue to investigate is the role of ASICs in disorders involving an increase in dopamine release, such as schizophrenia. The paper published by the Grunder laboratory suggests that ASIC1a may modulate dopamine secretion from human dopaminergic neurons (Neuhof et al, 2021 ). Schizophrenia is hypothesized to occur due to an over secretion of dopamine in the mesolimbic pathway (Birtwistle and Baldwin, 1998 ; Jones et al, 2011 ; Howes et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study published in Frontiers in Cellular Neuroscience from the Grunder laboratory has explored the role of ASICs in the differentiation of LUHMES cells (Neuhof et al, 2021 ). They first converted LUHMES cells into post-mitotic dopaminergic neurons and subsequently isolated ASIC mRNA.…”
Section: Functional Asics Modulate the Differentiation Of Luhmes Cellsmentioning
confidence: 99%
See 1 more Smart Citation